Response of crop seed germination and primary root elongation to a binary mixture of diclofenac and naproxen - Kummerová, Marie (Ecotoxicology (London, England), 2024)
© 2024. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.